2004
DOI: 10.1002/pat.517
|View full text |Cite
|
Sign up to set email alerts
|

Poly(caprolactone triol) as plasticizer agent for cellulose acetate films: influence of the preparation procedure and plasticizer content on the physico‐chemical properties

Abstract: The influence of the plasticizer content and film preparation procedure on the morphology, density, thermal and mechanical properties of cellulose acetate (CA) films plasticized with poly-(caprolactone triol) (PCL-T), were studied. Differential scanning calorimetry (DSC), thermal mechanical analysis (TMA), scanning electron microscopy (SEM), wide-angle X-ray diffraction (WAXD) and infrared spectroscopy (FT-IR) techniques were used. The films were prepared by dry-casting CA and CA/PCL-T in acetone or acetone/wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 23 publications
7
49
0
5
Order By: Relevance
“…Aparentemente, a presença de 30% de sorbitol reduziu as interações polímero-polímero, aumentando o volume livre entre as cadeias, promovendo a diminuição no módulo de elasticidade. Comportamento similar foi observado por Meier et al 52 no estudo do efeito da poli (caprolactona triol) nas propriedades mecânicas de filmes de acetato de celulose. Para os filmes de alginato reticulados, o módulo de elasticidade diminui de 524 para 420 MPa com a quantidade de sorbitol variando de 0 para 10%, respectivamente, permanecendo praticamente constante na faixa de 10 a 30% de sorbitol, sugerindo a formação de filmes mais resistentes.…”
Section: Propriedades Mecânicasunclassified
“…Aparentemente, a presença de 30% de sorbitol reduziu as interações polímero-polímero, aumentando o volume livre entre as cadeias, promovendo a diminuição no módulo de elasticidade. Comportamento similar foi observado por Meier et al 52 no estudo do efeito da poli (caprolactona triol) nas propriedades mecânicas de filmes de acetato de celulose. Para os filmes de alginato reticulados, o módulo de elasticidade diminui de 524 para 420 MPa com a quantidade de sorbitol variando de 0 para 10%, respectivamente, permanecendo praticamente constante na faixa de 10 a 30% de sorbitol, sugerindo a formação de filmes mais resistentes.…”
Section: Propriedades Mecânicasunclassified
“…Apresenta-se como um polímero semicristalino com grau de cristalinidade (α c ), na ordem de 50% e temperatura de transição vítrea (T g ) em torno de -70 °C. Em geral, a PCL apresenta a capacidade de formar blendas com vários polímeros em um vasto campo de composições, e tem sido usada como plastificante polimérico [18][19][20] . Num estudo de biodegradação de filmes homopoliméricos de P(3HB), P(3HB-V) e PCL em solo, Rosa et al [21] verificaram que P(3HB) degradou mais rapidamente que PCL e P(3HB-V) não apresentou degradação no período avaliado de 90 dias.…”
Section: Introductionunclassified
“…PCL-T is a biodegradable aliphatic polyester with low molecular weight, moderate water solubility and melting temperature close 33 o C. 19 There are three hydroxyl groups to which the ability to plasticize some natural polymers, such as soy protein and cellulose acetate, is attributed. 20,21 Meier et al 7 showed that the addition of liquid PCL-T (Mw 300 g/mol) to cellulose acetate films modulates drug permeability through a decrease in the polymer-polymer interactions (plasticizing effect) and the formation of small pores and channels through PCL-T dissolution .…”
Section: Introductionmentioning
confidence: 99%
“…21 EMA is an elastomeric copolymer composed of ethylene and methyl acrylate units, which are crystalline and amorphous, respectively. 22 EMA, just like EVA, has good mechanical properties for the development of controlled-drug release systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation